Pengaruh Economic Order Quantity (EOQ) terhadap Pengendalian Persediaan Bahan Baku di PT. Vinrell Indonesia Persada di Cikarang Utara - Dewi, Sekar Sandra; Utami, Noviandari Sari; Chaerunisyah, Ana; Patria, Yoka Mai; Sapta, Adjie (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2024)
The raw material inventory control system at PT. Vinrell Indonesia Persada has not been well-planned, resulting in raw materials running out during the production process. Excessive orders of raw materials often occur, leading to changes in texture that render them unusable. This research aims to determine the extent of the influence of Economic Order Quantity (EOQ) on raw material inventory control at PT. Vinrell Indonesia Persada in North Cikarang. The study employs a quantitative research approach with a descriptive method. The population consists of 20 employees of PT. Vinrell Indonesia Persada, and a non-probability sampling technique, namely saturation sampling, is utilized. The discussion includes calculations assisted by the SPSS for Windows Version 26 computer program. The research results indicate a positive influence between the Economic Order Quantity variable and the effect on raw material inventory control by 10.5%, while the remaining 89.5% is explained by other variables outside the scope of this study. The hypothesis test results show that the t-value > t-table (1.452 > 3.1), indicating the rejection of H0 and the acceptance of H1, or there is an influence between Economic Order Quantity and the effect on raw material inventory control.